Antibiotics use evaluation among hospitalized adult patients at Jimma Medical Center, southwestern Ethiopia: the way to pave for antimicrobial stewardship - Mesay Dechasa; Legese Chelkeba; Amente Jorise; Birbirsa Sefera; Tsegaye Melaku (Taylor & Francis Group, 2022)
Background An irrational antibiotic use is a common problem in developing countries like Ethiopia, which makes empiric antibiotics use difficult. It is considered to be the greatest health problem in our time and future unless intervened. Therefore, this study aimed to assess the patterns of antibiotics use among hospitalized adult patients to pave the way for antimicrobial stewardship. Methods A hospital-based prospective observational study was conducted at Jimma Medical Center, southwestern Ethiopia, from 30 October 2020 to 29 January 2021 with 360 adult hospitalized patients participating. A semi-structured questionnaire and consecutive sampling technique was used for data collection. The data were collected through medical record reviews and patient interviews. The collected data were entered into Epi-data and exported to SPSS® version 23.0 for analysis. Days of therapy (DOT) and essential medicine lists "Access, Watch, and Reserve (AWaRe)" antibiotics classification were used to assess antibiotic use pattern among participants. Results The majority of study participants were females (55.3%), attended formal education (59.4%), and live in rural areas (61.4%) with mean age ± (SD) of 37.65 ± (16.75). The overall rate of antibiotics consumption during the study was 111 days of therapy per 100 bed-days and about two-thirds (66%) of the prescribed antibiotics were from the "Watch" group antibiotics. The indicator level of antibiotics use for "Access" group antibiotics was 34% in this study based on the World Health Organization Essential Medicine List. Cephalosporins were the most commonly used class of antibiotics (93.9%). Conclusion Higher antibiotics exposure and their consumption frequently observed among adult hospitalized patients in the study setting. There was a rapid increase in "Watch" group antibiotics use and about two-thirds of the prescribed antibiotics were from this group. The third-generation cephalosporin were the most commonly used class of antibiotics. Generally, higher consumption and inappropriate antibiotics use among hospitalized adult patients showed the need for urgent interventions by implementing Antimicrobial Stewardship Programs in hospitals.